1987
DOI: 10.1126/science.3823879
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Antibody Binding to a Protein

Abstract: The mechanisms of antibody binding to a protein were studied by an analysis of specific amino acid residues critical to nine antigenic sites on myohemerythrin. Rabbit antisera to the whole protein were assayed for binding to more than 1500 distinct peptide analogs differing from the protein sequence by single amino acid replacements. The results, combined with information from the three-dimensional crystallographic structure, were used to evaluate probable mechanisms of antibody binding at individual sites. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(81 citation statements)
references
References 43 publications
5
76
0
Order By: Relevance
“…Another possibility is main chain elements involved in some unusual turn or chain reversal within the amyloid motif. Detailed structures of the epitopes of anti-protein Abs are normally characterized either by protein crystallography (42) or by mutational analysis of antigen fragments (43) or intact protein (44). Because amyloid has yet to be crystallized, and because WO1 and WO2 bind to many amyloids regardless of amino acid sequence, it is clear that the further structural analysis of the WO1͞WO2 epitope(s) will be challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility is main chain elements involved in some unusual turn or chain reversal within the amyloid motif. Detailed structures of the epitopes of anti-protein Abs are normally characterized either by protein crystallography (42) or by mutational analysis of antigen fragments (43) or intact protein (44). Because amyloid has yet to be crystallized, and because WO1 and WO2 bind to many amyloids regardless of amino acid sequence, it is clear that the further structural analysis of the WO1͞WO2 epitope(s) will be challenging.…”
Section: Resultsmentioning
confidence: 99%
“…It is of interest to know whether the conformational change adopted by a loop (a side chain, ligand, etc.) upon binding has been induced by the other protein (induced fit 5,6 ) or alternatively the free loop already interconverts among different microstates where one of them is selected upon binding (selected fit 7 ). This analysis requires calculating p m values, which are also needed for a correct analysis of NMR and X-ray data of flexible macromolecules.…”
Section: I1 the Role Of Free Energy In Structural Biologymentioning
confidence: 99%
“…This indicated that deformation of the antigen induced by binding to the trapping antibody influenced recognition by monoclonal antibody. Structural differences induced by antibody binding have been demonstrated in other protein systems (Getzoff et al, 1987). SB2 provided a negative control because no differentiation was evident between top, middle or bottom components in the affinity assay or the liquid phase competition assay.…”
mentioning
confidence: 99%